Design and analysis of a microstrip patch antenna at 7.5 GHz for X-band VSAT application - Mohamad, Sarah Yasmin; Muzamil, Noralya Fatin; Abdul Malek, Norun; S. M. A., Motakabber; Abd Malik, Rafidah; Shuhaimi, Nurain Izzati (IIUM, 2022)
In this paper, a microstrip patch antenna is designed to be used for X-band VSAT application at 7.5 GHz. The antenna is proposed to replace the massive and commonly used parabolic reflector antennas (46.0 inch × 29.3 inch × 13.5 inch (116.84 cm × 74.42 cm × 34.29 cm) with weight of 66.2 kg) in terms of portability due to its compact and lightweight features, with overall dimensions of 19.00 mm × 30.55 mm. The 7.5 GHz frequency is chosen based on the X-band frequency used in Malaysia, as reported by STRIDE. The microstrip patch antenna is first designed and simulated using CST Microwave Studio (CST MWS) and exhibits a good return loss (S11) of -42.09 dB, a bandwidth of 399 MHz, directivity of 7.63 dB and gain of 7.18 dB. The antenna is then fabricated using RT/duroid ® High Frequency 5880 substrate with a dielectric constant of εr = 2.2, loss tangent of δ = 0.0009 and thickness of t = 1.574 mm. Next, the return loss and radiation pattern measurements are carried out to confirm the simulated results. The measurement of the antenna prototype provides a return loss S11 of -30.53 dB, bandwidth of 455 MHz, directivity of 5.51 dB and gain of 3.88 dB.